The school principal in Argentina: A key (yet) invisible actor. A study on regulations, work conditions and professional development of school principals in public schools - Claudia Romero; Gabriela Krichesky (Arizona State University, 2019)
School leadership is strategic for educational policy. Specialized research has produced, over the last decade, strong evidence regarding the centrality of school leadership in improving teaching and achieving good learning outcomes, and is defined as the "second most important school related factor". However, in Latin America in general and Argentina in particular, this contrasts with the lack of systematic research on the subject and even more with either the absence or isolated policy initiatives aimed at improving school leadership. This article gathers central data from a study which focused on producing and analyzing relevant information on school leadership in Argentina, and is based primarily on three dimensions: (a) legislation that defines the functions and responsibilities of school leaders, (b) employment and recruitment conditions to which they are subject, and (c) provision of training programs for school leaders. Even with the limitations of the case, due to the fact that the study is entirely based on the public sector, which represents 70% of the educational offer, this article offers essential information to understand the current situation of school leaders in the country and is a contribution to further regional compared analysis and the production of policies aimed at developing, strengthening and professionalizing school leadership as a factor for school improvement.